Analysis of The Needs For Local Wisdom-Based Literacy Learning Media in Gunungkidul - Ragil Dian Purnama Putri; Prahita Filma Ayuningtyas; Tri Lestari (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aimed to analyze the needs for local wisdom-based reading and writing literacy learning media in SD Negeri Bulu Playen, Gunungkidul. The study employed a descriptive qualitative approach involving the principal, fifth-grade teacher, librarian, computer laboratory staff, and fifth-grade students as research subjects. Data were collected through observations, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source triangulation and technique triangulation. The results showed that reading and writing literacy activities had been routinely implemented through various approaches, such as 15–30-minute literacy sessions, use of the library and classroom reading corners, Chromebook-assisted literacy activities, and book identification activities. However, the implementation of literacy activities had not been supported by learning media that suited students’ characteristics and the local cultural context. The needs analysis revealed that the required learning media included printed media in the form of regional profile books, folklore, and local tradition stories; audio-visual media in the form of videos about geographical conditions, local traditions, and traditional food-making processes; and interactive media containing educational games and local wisdom-based exercises. The development of local wisdom-based learning media is expected to improve students’ reading and writing literacy skills, motivation to learn, and appreciation of local culture.